ANALISIS PENENTUAN PORTOFOLIO OPTIMAL DENGAN MENGGUNAKAN MODEL MARKOWITZ PADA PERUSAHAAN SEKTOR PERBANKAN YANG TERDAFTAR DALAM INDEKS LQ45 DI BURSA EFEK INDONESIA - Kirana Amalia Latulanit; Mohammad Amin; Muhammad Cholid Mawardi (Universitas Islam Malang, 2018)
ABSTRACTIn stock investment activities in the capital market, an investor needs tohave expertise in minimizing the level of investment risk that must be borne. Oneway that can be done by investors to minimize the risk level is to form a portfolio.the determination of the shares of the candidate portfolio can be done using theMarkowitz model. The value of expected return is the value used as the basis forcalculating the Markowitz model. This study using six samples of banking sectorcompanies of BEI which selected by using purposive sampling method. Sampleselection results show that of the six shares of the banking sector companies thereare five shares of banking companies that can be used as a portfolio candidate. Inthis study, five candidates of the company's optimal portfolio stocks are the sharesof BBCA (Bank Central Asia Tbk), BBNI (Bank Negara Indonesia Tbk), BBRI(Bank Rakyat Indonesia Tbk), BMRI (Bank Mandiri Tbk) and BBTN (BankTabungan Negara Tbk). from the establishment of this portfolio obtained portfolioreturn rate of 16.21% and portfolio risk level or standard deviation that reachedthe lowest point of 0.64%.Keywords: investment, optimal portfolio, Markowitz model